The influence of incident and reflected potential wave on the point vortex evolution near a solid surface - Kulik, K.N.; Tur, A.V.; Yanovsky, V.V. (Вопросы атомной науки и техники, 2007)
The influence of oscillation potential modes upon the point vortex movement near a solid wall is studied. The equations describing the point vortex movement in the given field of a potential wave in the presence of a solid wall are obtained. The character of the vortex movement is shown to change qualitatively under the influence of a potential wave. All the possible modes of vortex movement under the influence of a potential wave are analyzed.